10/112
Rozwiąż podane układy równań dowolną metodą

a) y + 2 - ( 3 - x) = 0
x - 2 = 5 - ( 2 - y)


b) 3 ( x -y) + 4x = 8
3 ( x - 5y) = 5 - 9y

c) 3 ( 2x - 1) + 4 ( y - 2 ) = 9
2 ( 5x - 1) + 3y = 5( 3x + y)+ 2

d) 2 ( x +y) - 3 ( x - 2y) = -7x - 2
5( x+1) -2 ( 3 - y) = -4 ( x+ y)

e) 4 (x +2) -3( y-1) = x +y -3
3(x-4) -2 ( y-2) = 4 (x - y)+ 4

11/112

a) 3 ( x - 1/2) + 2 ( y +3) = 3 1/2 ( 3,5)
3x - 1 / 3 - y+3/ 2 = - 1 ( 3x - 1 i y+3 to liczniki ;) )


b) x-3/4 - y+5/2 = - 1,5 ( y+5 to licznik)
x - 3 / 2 - 2y -7 /3 = 1 ( 2y-7 to licznik)


c) 2x -5/2 - x-6y/4 = x+y / 2 ( x- 6y to licznik)
3x-1 /10 + 2y-5/5 = 2x +y/ 2 ( 2y -5 to licznik) (3x-1 licznik)

d) x-3/5 - y+1/2 = 1 - ( x- y) ( y + 1 to licznik) (x -3 to licznik)
4x-1 /3 - y-3/6 = -2 (x-y) ( 4x - 1 to licznik) ( y-3 to licznik)

/ - kreska ułamkowa

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-05T18:04:03+01:00
10
a)
y+2-(3-x)=0
x-2=5-(2-y)

y+2-3+x=0
x-2-5+2-y=0

x+y=1 ----->x=1-y
x-y=5

1-y-y=5
-2y=4
y=-2
x=1-(-2)
x=3
b)3x-3y+4x=8
3x-15y=5-9y

7x-3y=8 /*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5
_____________
-11x=-11
x=1
7*1-3y=8
-3y=8-7
-3y=1
y=-1/3
c)6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=20
-5x-2y=4 /*2

6x+4y=20
-10x-4y=8
___________
-4x=28
x=-7
6*(-7)+4y=20
4y=62
y=15,5
d)2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

6x+8y=-2 /*(-9)
9x+6y=1 /*6

-54x-72y=18
54x+36y=6
__________
-36y=24
y=-2/3
6x+8*(-2/3)=-2
6x=-2+16/3
6x=-6/3+16/3
6x=10/3
x=5/9
e)
4x+8-3y+3-x-y=-3
3x-12-2y+4-4x+4y=4

3x-4y=-14
-x+2y=12 *3

3x-4y=-14
-3x+6y=36
__________
2y=22
y=11
3x-4/11=-14
3x=30
x=10

85 3 85
2009-12-05T18:40:36+01:00
Zad 10
a) y + 2 - ( 3 - x) = 0
x - 2 = 5 - ( 2 - y)

y+2-3+x=0
x-2=5-2+y

x+y=-2+3
x-y=5-2+2

x+y=1
x-y=5

x=6
y=0

b) 3 ( x -y) + 4x = 8
3 ( x - 5y) = 5 - 9y

3x-3y+4x=8
3x-15y=5-9

7x-3y=8 /*3
3x-6y=5 /*(-7)

21x-9y=24
-21x+42y=-35

33y=-11
y=- 11/33
y=-1/3

7x-3y=8 /*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5

-11x=-11
x=1

c) 3 ( 2x - 1) + 4 ( y - 2 ) = 9
2 ( 5x - 1) + 3y = 5( 3x + y)+ 2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=9+8+3
10x-15x-5y+3y=2+2

6x+4y=20 /*5
-5x-2y=4 /*6

30x+20y=100
-30x-12y=24
8y=124
y=15,5

6x+4y=20
-5x-2y=4 /*2

6x+4y=20
-10x-4y=8
-4x=24
x=-7

d) 2 ( x +y) - 3 ( x - 2y) = -7x - 2
5( x+1) -2 ( 3 - y) = -4 ( x+ y)

6x+8y=-2
9x+6y=1

-54x-72y=18
54x+36y=6
-36y=24
y=-2/3

6x+8y=-2
9x+6y=1

-18x-24y=-6
36x+24y=1
18x=-5x
x=-5/18




34 3 34